Case report: High-risk acute promyelocytic leukemia and COVID-19-related myocarditis one patient, two cytokine storms - Ghiaur, Alexandra; Doran, Cristina; Ionescu, Bogdan; Mohorea-Neata, Lacramioara –Andreea; Stancioaica, Camelia; Hirjan, Roxana; Tatic, Aurelia; Cirstea, Mihaela; Vasilache, Didona; Tabac, Dana; Lupescu, Ioana; Coriu, Daniel (Frontiers in Oncology, 2023)
Abstract Acute promyelocytic leukemia (APL) is a unique, highly curable subtype of acute myeloid leukemia, owing to the therapeutic advances of the last decades which led to high complete remission rates and excellent long-term survival. Nevertheless, it remains associated with high early mortality rates. Early death is the major cause of treatment failure in APL and is mainly attributed to coagulopathy, differentiation syndrome, and less commonly, infectious events. Timely recognition of each complication plays a crucial role in the management of patients diagnosed with APL. Coronavirus Infectious Disease 2019 (COVID-19) has shown great heterogeneity in patient presentation. Clinical manifestations range from asymptomatic disease to severe forms, mainly characterized by a hyperinflammatory syndrome leading to acute respiratory distress and multiorgan failure. Patients with acute leukemia and concomittant COVID-19-related hyperinflammatory syndrome have particularly poor outcomes. We hereby report the case of a 28-year-old male patient who was diagnosed with high-risk APL, with severe associated coagulopathy at presentation. He was treated with chemotherapy according to the AIDA regimen. The first week of induction therapy was complicated by a differentiation syndrome manifesting as fever not attributable to infection and respiratory distress with pulmonary infiltrates, resolved after ATRA discontinuation and corticotherapy. On the fourth week of treatment, he tested positive for acute respiratory syndrome coronavirus 2 (SARS-CoV-2) with minor pulmonary involvement. Clinical manifestations over the following days included tachycardia and hypotension, associated with elevated inflammatory markers and cardiac biomarkers (troponin I x58 upper NV). Cardiovascular magnetic resonance imaging was consistent with myocarditis. COVID-19-associated myocarditis was successfully treated with methylprednisolone, intravenous immunoglobulins and Anakinra. Differentiation syndrome and COVID-19-associated myocarditis are two life-threatening complications that adversely impact survival. However, early recognition and prompt treatment initiation can improve clinical outcomes, as was the case of our patient.